區間價格下公開市場股票買回之評價：互換選擇權之應用 - 蔡佩玲; 林士貴; 池祥萱; Pei-Ling Tsai; Shih-Kuei Lin; Hsiang-Hsuan Chih (My University, 2012)
互換選擇權（exchange option）為提供投資人將已擁有資產轉換成另一種資產之權利。Ikenberry and Vermaelen（1996）指出管理者在公司股價被低估時，公司會在公開市場宣告OMR（open market repurchases）計畫，未來將於公開市場上買回股價被低估的股票，亦即將股票被低估之市場價值和其真實價值做交換，此為互換選擇權之概念。然而，台灣上市公司宣告OMR計畫和其他國家不同點在於台灣上市公司宣告OMR計畫時必須同時宣告「區間價格」，亦即在宣告日公布區間價格上限與下限，也就是股價介於此區間價格才能在市場買回庫藏股。因此，本文在理論方面推導區間價格之互換選擇權價值。在數值方面有二個結果，第一，區間價格上下限距離越大OMR計畫訊息宣告市場反應越大。第二，將價格下限及價格下限設在使用牛頓法計算出之理論價格下限及理論價格下限即可，因此本文使用牛頓法計算出之理論價格下限及理論價格上限為合理的參考指標。實證分析上有三個結果，首先，公司宣告OMR計畫以拉抬股價為主，投資人比較相信高價而不是低價。第二，區間價格模型有較高的解釋能力，因此在評價宣告OMR計畫價值時，應加以考慮宣告買回之區間價格。最後若公司實際宣告的價格上限越接近理論最適價格上限，市場反應是顯著的，表示本文計算之理論價格上限是良好的參考指標。

Managers have the option to repurchase the stocks by the announcement of an OMR (open market repurchases) if they feel the company's stock price is undervalued. The market price of the stocks is exchanged for the true value of the stocks and is considered as an exchange option developed by Ikenberry and Vermaelen (1996). However, the announcement of an OMR for listed companies in the TSE (Taiwan Stock Exchange) is distinguished from other stock exchanges in making a simultaneous announcement of the ”interval of repurchase price”. Under considering of Taiwan's law, this paper uses the exchange option to provide the evaluation of an OMR program. Based on the results of numerical analysis, the bigger the gap between the lower limited price and the upper limited price is, the more intense the market response toward the OMR announcement will be. The theoretical lower limited price and the theoretical upper limited price of using the Newton's method to obtain are selection guideline. The major findings in empirical study are as follows: First, investors tend to believe the upper limited price announced by the OMR firms can be achieved, that is, the investors also think that the company's stock price is undervalued. Second, the interval of repurchase price should be considered by evaluating the exchange option value of OMR announcements. Finally, the cumulated abnormal return on stocks is significant by being different from zero when the actual upper limited price is close to the theoretical upper limited price. Consequently, the theoretical upper limited price of the paper provides a selection guideline to companies making repurchase decisions.
Valuation of Open Market Repurchases with Interval Prices: An Application of the Exchange Option
Keywords: 公開市場股票買回; 互換選擇權; 區間價格; Open Market Repurchases; Exchange Option; Interval of Repurchase Price